Relasi Agama Dan Negara: Telaah Pemikiran Politik Soekarno Dan Fazlur Rahman - Sudarti Sudarti (Prodi Tata Negara (Siyasah) IAIN Langsa, 2020)
The author in this study wanted to see the similarities and differences in the political thoughts of Soekarno and Fazlur Rahman about the relationship between religion and the state. The type of research used is library research with a descriptive-comparative method. The results showed that Soekarno and Fazlur Rahman had a different paradigm in viewing the relationship between religion and state. Soekarno has a secularistic paradigm that separates religion and state to be implemented in Indonesia, while Fazlur Rahman has an Integralistic paradigm in which religion (Islam) and the state cannot be separated (integrated). However, these two figures agree that the sovereignty of a country is in the hands of the people and do not agree with the theory of God's sovereignty because God has never acted as politically sovereign nor as a maker of laws or laws. Keywords: Secularistic Paradigm, Integralistic Paradigm, God's Sovereignty.